ANALISIS PROBLEMATIKA PENDIDIKAN MATEMATIKA BERUPA SOAL CERITA PADA SISWA SD - Satrio Wicaksono Sudarman (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2016)
This study is intended to determine problemtika types of errors in math story problem solving in elementary school student. This type of research is descriptive qualitative research. In a descriptive study is essentially a method used to find specific data and the reality of what happened in the community at a particular time. To find the errors do math word problems can be analyzed on a step by step process of the students completed the test questions were given. in some cases comprehension students about about the story on which this study, students' difficulties phrased sentence of math word problems, difficulty in terms of actual in description story for students in the following ways; (1) Students with lower language understanding, it is very difficult to digest towards the goal of every sentence in the matter of the story. Going where and what to do with the sense of the question is very vague and unclear. So the mindset of students just spinning on the same premises. (2) The concept is not yet strong prerequisite for solving problems related to the concept of prerequisite